Enhancing English Language Learning Process through Drama Activities : A Focus on Oral Production (2024)
ABSTRACT: This action research aimed to promote students’ oral production by integrating drama activities into English classes. The project was carried out with fifth graders at Sor Juana Inés de la Cruz Educational Institution. Some of the strategies implemented included activities such as body and facial expression games, relaxation exercises, scriptwriting, character and scene role-play through theatrical scripts, and cooperative work. The data collection methods involved field diaries (journals), two student questionnaires, student artifacts, and the cooperating teacher’s journals. These instruments were analyzed through coding and categorization to identify the main findings. The results highlighted the positive influence of integrating drama activities, as they allowed students to improve their oral skills while also enhancing their ability to interact and collaborate with one another.